IMPLEMENTATION OF PROTOTYPING PROCESS MODEL IN TASK MANAGEMENT APPLICATION AND OBJECTIVE KEY RESULT CASE STUDY PT.XYZ - Rosalin Samihardjo; Yoki Anggadita; Eri Nugraha (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Managing tasks in a company is a crucial thing to do, considering the number of functions that exist in that company. PT.XYZ does not have a task management application that causes task complexity to occur frequently for each employee so that the employee performance evaluation cannot be objective. One alternative solution proposed is to approve the task management application and objective key results by implementing the prototyping process model at PT. XYZ so that it can produce approval of application requirements, design data, design architectures, and design applications that can support objective employees.